Disposable Biomimetic Array Sensor Strip Coupled With Chemometric Algorithm For Quality Assessment Of Orthosiphon Stamineus Benth Samples - Yap, Maxsim Mee Sim (2006)
A disposable screen printed array sensor strip based on self-plasticized methacrylate acrylate PVC blend lipid membranes combined with chemometric algorithm has been developed and applied for qualitative and quantitative analysis of O.stamineus samples. For qualitative analysis, the biomimetic array sensor system combined with Principal Component Analysis (PCA) and Discriminant Analysis (DA) were able to classify and to verify the geographical origin of the herbal samples. The classification model built with PCA was useful for the discrimination of the herb according to its parts; stem and leaves, while was also successfully applicable for different type of O.stamineus extracts identification. PCA has also been applied for batch to batch consistency screening of the herb while model built with DA on the other hand was able to predict the taste of O.stamineus sample which was found to be bitter taste based on the five basic taste qualities. For quantitative analysis, Partial Least Square (PLS) and Principal Component Regression (PCR) were applied to the array sensor output to determine whether the content of sinensetin and caffeic acid in different batches of O.stamineus extracts could be obtained by these methods. Comparison between the PLS and PCR models presented in the quantitative analysis showed that PLS have substantially better predictive capability than PCR and the results obtained were in good correlation with the results given by the HPTLC method.